Perusahaan Manufacture Execute System Pada PT. Human Touch Management Indonesia - Hariko Saputra (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
Manufacturing companies are companies that focus on the production of a product. PT. Human Touch Management Indonesia is a shoe company located in Tangerang. Production monitoring at the company is still done manually. For this reason, the author created a Manufacturing Execute System (MES) which focuses on monitoring production starting from the cutting, sewing, and assembling to finishing processes. This system aims to control the entire production process quickly and accurately in real-time. This Manufacturing Execute System was created using the PHP programming language and Microsoft SQL Server 2016 database.